When environmental protection and human rights collide : the politics of conflict management by regional courts / Marie-Catherine Petersmann. - Petersmann, Marie-Catherine (Cambridge studies in international and comparative law (Cambridge, England : 1996) ;, 2022)
Conflicts between environmental protection laws and human rights present delicate trade-offs when concerns for social and ecological justice are increasingly intertwined. This book retraces how the legal ordering of environmental protection evolved over time and progressively merged with human rights concerns, thereby leading to a synergistic framing of their relation. It explores the world-making effects this framing performed by establishing how 'humans' ought to relate to 'nature', and examines the role played by legislators, experts and adjudicators in (re)producing it. While it questions, contextualises and problematises how and why this dominant framing was construed, it also reveals how the conflicts that underpin this relationship - and the victims they affect - mainly remained unseen. The analysis critically evaluates the argumentative tropes and adjudicative strategies used in the environmental case-law of regional courts to understand how these conflicts are judicially mediated, thereby opening space for new modes of politics, legal imagination and representation.